TRADISI PENDIDIKAN DAN PENANAMAN AKHLAK DI PONDOK PESANTREN DALAM MEMBANGUN PENDIDIKAN KARAKTER DI ERA POST MODERN - Muhammad Yusuf; Ali Arifin; M. Slamet Yahya (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
The purpose of this article is to map and describe the role of Islamic boarding schools, which are built within a tradition of Islamic boarding schools as well as inculcating moral values ​​in Islamic boarding schools in an effort to instill character education in the current post-modern era and possibly in the future. This article uses a type of literature research by collecting writings about the role of Islamic boarding schools in the formation of the character of a santri supported by the main elements of Islamic boarding schools, namely the presence of kyai (main teacher). The education system and the cultivation of moral values ​​in Islamic boarding schools cannot be separated from the role of the kyai, who physically educates and instills noble moral character in each of his students. Islamic boarding schools must play themselves as guardians and preservers of religious values and as reformers of religious understanding and social education in the global or post-modern era.